Diversity, Equity and Inclusion: Are Linguistic Rights Respected in Taiwan? - Yeh, Hsin Jung (Trinity College (Dublin, Ireland). School of Languages, Literature and Cultural Studies, 2023)
The objective of this dissertation is to examine how Taiwanese authorities protect linguistic rights and embody the diversity, equity and inclusion (DEI) perspectives in the policy documents Bilingual 2030 (National Development Council et al., 2021) and National languages development plan 2022-2027 (Ministry of Culture et al., 2022). As language planning and policy in Taiwan shift according to different types of political regimes and ideologies, linguistic rights do not always fall within the scope of human rights, and some groups are excluded. Therefore, it is important to study whether linguistic rights are supported in the current language planning and policy. Employing a qualitative research approach, this research firstly reviews the Taiwanese socio-historical context and its ethnolinguistic composition and takes Ruiz's (1984) language planning orientations framework to look at the transformation of language attitude in Taiwan. This dissertation then comparatively analyses two policy documents and discusses the four domains where the linguistic rights are applied: public services, encouragement measures in the community, education, and technology use and media. The critical discourse analysis is used to explore the similarity and differences between two selected documents, investigating the presence and absence of diversity, equity and inclusion perspectives, as well as identifying what language ideology is presented in the current language policies. This research argued that the language ideology has shifted from language-as-problem to language-as-right and language-as-resource orientation, since the concept of language equality was taken into account in some measures stated in the policies. However, neither of the two policies fully supports linguistic rights from the perspective of DEI.
Keywords: Applied Intercultural Communications